2003
DOI: 10.1037/0278-7393.29.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Pure perceptual-based sequence learning.

Abstract: Learning a sequence of target locations when the sequence is uncorrelated with a sequence of responses and target location is not the response dimension (pure perceptual-based sequence learning) was examined. Using probabilistic sequences of target locations, the author shows that such learning can be implicit, is unaffected by distance between target locations, and is mostly limited to first-order transition probabilities. Moreover, the mechanism underlying learning affords processing of information at antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
143
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(156 citation statements)
references
References 88 publications
(131 reference statements)
11
143
2
Order By: Relevance
“…This observation of implicit pure perceptual-based sequence learning is in accord with previous behavioral results (Remillard, 2003(Remillard, , 2009Goschke and Bolte, 2007;Abrahamse et al, 2008Abrahamse et al, , 2009. In most of the previous studies, volunteers implicitly learned a sequence of stimulus locations, which could entail the oculomotor system and therefore might also at least partially involve motor learning.…”
Section: Discussionsupporting
confidence: 78%
“…This observation of implicit pure perceptual-based sequence learning is in accord with previous behavioral results (Remillard, 2003(Remillard, , 2009Goschke and Bolte, 2007;Abrahamse et al, 2008Abrahamse et al, , 2009. In most of the previous studies, volunteers implicitly learned a sequence of stimulus locations, which could entail the oculomotor system and therefore might also at least partially involve motor learning.…”
Section: Discussionsupporting
confidence: 78%
“…The classic and most often employed version however uses spatially oriented targets. For spatial targets, some studies have shown that purely perceptual sequence learning does occur (Howard et al, 1992;Mayr, 1996;Remillard, 2003) while some studies have shown that it does not (Willingham et al, 1989;Willingham, 1999;Kelly and Burton, 2001). In instances where perceptual learning has been found to occur, it has been unclear whether increases in performance were in fact attributable to perceptual learning, or were reflections of spontaneous increases in explicit awareness or oculomotor sequence learning.…”
Section: Introductionmentioning
confidence: 97%
“…They respond faster to targets appearing in more predictable locations, either because these target locations have higher marginal frequencies (Geng & Behrmann, 2002Jones & Kaschak, 2012) or because they are linked to stronger transition probabilities (Remillard, 2003(Remillard, , 2009). We therefore expected that being able to predict location transitions would serve as an endogenous cue, resulting in increased activity in regions associated with recruitment and directing of spatial attention, specifically the bilateral intraparietal sulcus and the frontal eye fields (see Corbetta &Shulman, 2002, andalso Szczepanski &Kastner, 2013, for recent review).…”
Section: Introductionmentioning
confidence: 99%